A Method ·for the Preparation of Cooked Peeled- Fronzen Prawns. - MATHEN, CYRIAC; MATHEW, ANNAMMA; VARMA, P.R GIRIJA; THOMAS, FRANCIS (Fishery Technology, 2017)
Several consignments of cooked-peeled-frozen prawns exported from India were rejected last year due to high total plate count (TPC) at 30°C. The specified temperatureof incubation for TPC in our country is 37°C. Hence the effect of incubationat 30 and 37"C on TPC was studied. It is seen that the count is higher on incubationat 30°C. A method for production of cooked-peeled-frozen prawns conformingto the specification for TPC at 30°C is standardised and is reported. It consistsof recooking the cooked-peeled prawns followed by packing and freezing withoutfurther contamination. The method minimises batch to batch or sample to sample variation in TPC